2008
DOI: 10.1179/136404608x361620
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characteristics of spheroidal graphite cast irons containing Ni and Mn with mixed ferrite and bainitic ferrite microstructure

Abstract: This study aims to clarify the influence of additive elements of Ni and Mn on tensile and impact properties of three kinds of spheroidal graphite cast irons (SG irons), which are as cast, annealed and austempered samples. Spheroidal graphite cast irons with Ni (0-4?5 mass-%) and Mn (0-0?5 mass-%) melted by a high frequency induction furnace and cast into a Y block CO 2 mould with 30 mm in thickness. From the viewpoint of heat treatment, tensile strength and hardness of SG irons become larger in the order of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…Cho et al 30) have reported that small additions (up to 0.3 wt.%) of Mo and Ni promote ferrite, while higher levels of these elements alone or in combination promote pearlite, as observed by Hsu et al 31) for Co and Ni, Nobuki et al 32) for Ni and Mn, Lacaze et al 33) for Ni and Yu and Loper 34) for Mo, Cu and Ni. Venugopalan and Alagarsamy 35) related the pearlite promoter effect of nickel to its effect on the eutectoid temperature.…”
Section: Effects Of Pearlite Promotersmentioning
confidence: 86%
“…Cho et al 30) have reported that small additions (up to 0.3 wt.%) of Mo and Ni promote ferrite, while higher levels of these elements alone or in combination promote pearlite, as observed by Hsu et al 31) for Co and Ni, Nobuki et al 32) for Ni and Mn, Lacaze et al 33) for Ni and Yu and Loper 34) for Mo, Cu and Ni. Venugopalan and Alagarsamy 35) related the pearlite promoter effect of nickel to its effect on the eutectoid temperature.…”
Section: Effects Of Pearlite Promotersmentioning
confidence: 86%
“…Neither of these reports gives any details on the nature of the matrix, namely, the amount of ferrite and pearlite. As a matter of fact, the only result found up to now for a fully ferritised matrix shows Ni to slightly decrease room temperature (RT) impact energy, 4 without any information on its effect on the brittle to ductile transition temperature.…”
Section: Introductionmentioning
confidence: 97%
“…The original data are however not available and other works on the effect of Ni show some incoherencies. Small additions of Ni were claimed to promote the formation of ferrite and increase ductility, 6 while other studies show the opposite 4,[7][8][9] conclusions that Ni increases Y and UTS. In a previous work on the effect of various additions on pearlitic nodular cast iron, 10 a statistical analysis appeared to show that the addition of Ni up to 1?2 wt-% decreases the UTS without affecting Y and elongation at rupture A.…”
Section: Introductionmentioning
confidence: 99%
“…8 However, neither in Angus' monograph nor in the ASM handbook did appear any details about the microstructure of the tested alloys, namely the pearlite content of the matrix. The only information on the effect of Ni found up to now for fully ferritic matrix is due to Nobuki et al, 10 who reported (their Fig. 8, 0?1%Mn series, annealed) that 3 wt-%Ni slightly decreases the impact energy at RT of notched samples while it does not change the impact energy at RT of unnotched samples.…”
Section: Introductionmentioning
confidence: 99%